Mechanical Mechanism and Propagation Law of Fissure-Tip Cracks of Large-Size Rock Specimens with Two Precut Fissures - Liming Yin; Ming Li; Wenbin Sun; Juntao Chen; Bin Liu; Ziqi Wang (Shock and Vibration)
The rock is a kind of geological medium with damages of different degrees including fissures, faults, joints, and other structural defects. Many underground rock engineering projects, such as mining and tunnel excavation, can break the three-dimensional stress balance state of rock mass and make it subject to two-dimensional or even one-dimensional stress, thus inducing stress concentration which leads to rapid failure. In order to investigate the failure law of the rock mass with such defects under two-dimensional stress, based on the similarity theory, we first prepared rocklike specimens with fissures featuring actual mechanical properties and then systematically analyzed the fissure-tip crack propagation and specimen failure law and mechanical mechanism under two-dimensional stress in view of the stress field theory. The results demonstrate that with the increase of load, the microcracks developed and propagated gradually, during which a number of branch paths were generated from the fissure tips of the specimens; the upper and lower cracks were connected first due to the main crack propagation, forming a sliding surface which caused the failure of the specimens, and the strengths of the specimens also fluctuated according to the different combinations of the fissure dip angles and rock bridge dip angles. In view of acoustic emission (AE), we calculated and obtained the spatial positions of stress peaks in each direction at the fissure tips; through comparison and analysis, the angle corresponding to the negative angle peak of the maximum circumferential tensile stress and the maximum radial tensile stress is basically the same as the angle of the main crack propagation direction generated from the preexisting fissure; it can be inferred that the tensile stress is the main stress inducing crack initiation and specimen failure, which is consistent with the physical characteristics of rock (resistant to compression but not tension). This may serve as a guidance for judging the direction along which new cracks are generated in a rock mass with double structural planes.